2006
DOI: 10.1021/jp062824u
|View full text |Cite
|
Sign up to set email alerts
|

Thermally Stable Amorphous Mesoporous Aluminophosphates with Controllable P/Al Ratio:  Synthesis, Characterization, and Catalytic Performance for Selective O-Methylation of Catechol

Abstract: Amorphous mesoporous aluminophosphates (AlPO) with P/Al molar ratio in the range 0.8-1.15 are synthesized by using the citric acid (CA) route and are systematically characterized using N(2)-adsorption, XRD, SEM, solid-state CP-MAS NMR, FT-IR, TG-DTA, CO(2)-TPD, and NH(3)-TPD. The characterization studies show that the change in P/Al ratio could affect the structure, texture, thermal stability, and surface acid-base properties of AlPO. Samples with a relatively low P/Al ratio (< or =1.0) exhibit uniform amorpho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 39 publications
0
51
0
4
Order By: Relevance
“…2B). It is known that the hysteresis loop in the partial pressure region from 0.4 to 0.8 is associated with framework mesoporosity, and the hysteresis loop at high partial pressure (P/P 0 [ 0.8) is indicative of textural mesoporosity and/or macroporosity, whereas the sharp increase in nitrogen uptake at P/P 0 [ 0.9 is indicative of a significant amount of interparticle mesoporosity [19]. These results suggest that the porosity of Mg x AlO and MgO should mainly arise from voids of small particles.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…2B). It is known that the hysteresis loop in the partial pressure region from 0.4 to 0.8 is associated with framework mesoporosity, and the hysteresis loop at high partial pressure (P/P 0 [ 0.8) is indicative of textural mesoporosity and/or macroporosity, whereas the sharp increase in nitrogen uptake at P/P 0 [ 0.9 is indicative of a significant amount of interparticle mesoporosity [19]. These results suggest that the porosity of Mg x AlO and MgO should mainly arise from voids of small particles.…”
Section: Methodsmentioning
confidence: 99%
“…Previously, such approach has shown some advantages on the preparation of a variety of porous materials, including silica, alumina, aluminophosphates, carbon, etc. [17][18][19][20]. Herein, the catalytic properties of the resultant Mg x AlO materials are studied for the gas-phase aldol condensation of acetone.…”
Section: Introductionmentioning
confidence: 99%
“…The use of a solid acid catalyst offers many advantages over the conventional route, including convenient separation of catalyst and product, catalyst reusability, reduction of waste, etc. Indeed mesoporous aluminophosphate solids have been reported to possess appropriate weak acid-base pairs to facilitate this reaction [57]. The vapour-phase reaction was carried out at 280 • C and the primary product was guaiacol.…”
Section: Applications Of Mesoporous Aluminophosphates and Metal Alumimentioning
confidence: 99%
“…By this strategy, some ordered mesoporous AlPOs with relatively high thermal stability have been obtained [4][5][6][7][8]. Additionally, the sol-gel route has also been developed to synthesize mesoporous AlPOs in the presence of organic additives [9][10][11][12]. The mesoporous materials obtained by this route, although lack of long-range order due to their amorphous characteristics, exhibit very high thermal stabilities and high specific surface areas [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Different kinds of materials have been investigated as catalysts for this reaction, including metal oxides [24,25], zeolites [26] and supported heteropoly acids [27]. Recently, we have found that the aluminophosphatebased materials, prepared by conventional precipitation method [28][29][30] and by citric acid route [11], have shown the catalytic potential in this vapor-phase reaction due to their suitable weak acid-base properties, and that the catalytic performance of the aluminophosphate-based catalysts is greatly dependent on the P/Al ratio and the synthetic method, which could affect the structures, specific surface areas and surface acid-base properties of these catalysts [11,30].…”
Section: Introductionmentioning
confidence: 99%